EXTERNAL AND INTERNAL LOAD OF COSTA RICAN HANDBALL REFEREES ACCORDING TO SEX AND GAME PERIODS - Randall Gutiérrez-Vargas; Jose Alexis Ugalde-Ramírez; Daniel Rojas-Valverde; María Müller-Thyssen; Jose Pino-Ortega (Federación Extremeña de Balonmano; University of Extremadura, 2021)
The purpose of this study was to analyze the external and internal load of Costa Rican handball referees according to sex and game periods. Nine referees (6 men and 3 women) were monitored during U19 handball matches, using an ultra-wide band local positioning system (UWB) and WIMUPro™ inertial units (IMU). The results showed a total distance of 4566.54±494.02 m (46.95% at 0-6 km/h, 32.97% at 6-12 km/h, 18.11% at 12-18 km/h and 1.96% >18 km/h). 1298.34±151.42 m/s2 accelerations and 1297.73±152.09 m/s2 decelerations were performed. Maximal speed was 19.63±1.85 km/h and average speed was 4.80±0.34 km/h. Player LoadRT was 50.53±9.39 UA. Maximal and average heart rate was 170.59±18.20 bpm 143.06±16.94 bpm respectively. 60% of the efforts were <80% of maximum heart rate. Total energy expenditure was 372.34±67.80 kcal. No significant differences were found in physiological variables between sexes, although men covered greater distance at 0-6 km/h. In the second periods the total distance (m/min), distance at 6-12 km/h, 12-18 km/h (m/min) and >18 km/h, average speed, impacts at 3-5g and >5g, Player LoadRT, and energy expenditure decreased. In conclusion, sex does not seem to affect the external or internal load, while the game period influenced on the external load.